Pelelangan Objek Jaminan Berupa Hak Guna Bangunan Yang Habis Masa Berlakunya - Mario Satria Nagara Hendra (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2024)
A legal relationship based on a building right as a security interest is a manifestation of the creditor's prudence in a debt agreement, and it gives rise to a property right. This type of property right is classified as a security property right and has several unique characteristics, including the creditor's preference right and, most importantly, the fulfillment of its right. This security interest as a form of property right can be extinguished due to several reasons, including the expiration of the right to the land that is being used as the object of the security. Creditor protection and debtor liability often become issues even up to the execution process. This article discusses the validity of the auction of a security interest where the right to the land has been extinguished and the legal protection of the security interest holder whose security interest on the land has been extinguished. Keywords: Mortgage Rights; Secured Creditor; Security Interest.